Evaluation of neodymium isotope analysis of human dental enamel as a provenance indicator using 1013 Ω amplifiers (TIMS). Issue 3 (May 2019) - Plomp, E.; von Holstein, I.C.C.; Koornneef, J.M.; Smeets, R.J.; Baart, J.A.; Forouzanfar, T.; Davies, G.R.
Abstract: Human provenance studies employing isotopic analysis have become an essential tool in forensic and archaeological sciences, with multi-isotope approaches providing more specific location estimates compared to single isotope studies. This study reports on the human provenancing capability of neodymium isotopes ( 143 Nd/ 144 Nd), a relatively conservative tracer in the environment. Neodymium isotope ratios have only recently been determined on human remains due to low concentrations in human dental enamel (ppb range), requiring thermal ionisation mass spectrometry (TIMS) using 10 13 Ω resistors. Dental elements (third molars) from 20 individuals born and raised in the Netherlands were analysed for Nd concentration ( n = 12) and Nd isotope ratios ( n = 15). The geological control on Nd isotope composition was examined using coupled Nd-Sr isotope analysis of the same third molar. Teeth from different geological environments were also analysed (Caribbean, Columbian, and Icelandic, n = 5). Neodymium elemental concentrations in dental elements ranged between 0.1 and 7.9 ppb (median 0.5 ppb). The Dutch 143 Nd/ 144 Nd ratios of the provinces of Limburg and Friesland were between 0.5118 and 0.5121, with Dutch 87 Sr/ 86 Sr ratios in agreement with the previously established local range (0.708–0.710). The current findings were compared to previously published results on Nd concentration and composition from Dutch individuals. The concentration of Nd and 143 Nd/ 144 Nd ratios were weakly correlated (R 2 = 0.47, n = 17) in Dutch human dental enamel. The majority ( n = 25, 83.3%) of individuals had Nd and Sr isotope values isotopically indistinguishable from the geological environment in which their third molars formed and mineralised. However, the Nd isotope ratios of the Icelandic individual and several Dutch individuals ( n = 4) suggested that Nd in enamel is not solely influenced by geological environment. In order for neodymium isotopes to be quantitatively applied in forensic and archaeological settings further analyses of individuals from various geographical regions with well-defined dietary Nd isotope data are required. Graphical abstract: Unlabelled Image Highlights: First evaluation of the potential of neodymium isotopes for human provenancing Provides insight in Nd concentration and isotope ratios in human dental enamel First study presenting Nd isotope ratios from multiple geological settings First study combining 143 Nd/ 144 Nd and 87 Sr/ 86 Sr ratios of the same dental element The use of 10 13 Ω resistors allows for greater precision analysis of small samples